Profile of malignant hyperthermia susceptibility reports confirmed with muscular contracture test in Brazil - Silva,Helga Cristina Almeida da (2019)
Abstract Background and objectives: Malignant hyperthermia is an autosomal dominant hypermetabolic pharmacogenetic syndrome, with a mortality rate of 10%–20%, which is triggered by the use of halogenated inhaled anesthetics or muscle relaxant succinylcholine. The gold standard for suspected susceptibility to malignant hyperthermia is the in vitro muscle contracture test in response to halothane and caffeine. The determination of susceptibility in suspected families allows the planning of safe anesthesia without triggering agents for patients with known susceptibility to malignant hyperthermia by positive in vitro muscle contracture test. Moreover, the patient whose suspicion of malignant hyperthermia was excluded by the in vitro negative muscle contracture test may undergo standard anesthesia. Susceptibility to malignant hyperthermia has a variable manifestation ranging from an asymptomatic subject presenting a crisis of malignant hyperthermia during anesthesia with triggering agents to a patient with atrophy and muscle weakness due to central core myopathy. The aim of this study is to analyze the profile of reports of susceptibility to malignant hyperthermia confirmed with in vitro muscle contracture test. Method: Analysis of the medical records of patients with personal/family suspicion of malignant hyperthermia investigated with in vitro muscle contracture test, after given written informed consent, between 1997 and 2010. Results: Of the 50 events that motivated the suspicion of malignant hyperthermia and family investigation (sample aged 27 ± 18 years, 52% men, 76% white), 64% were investigated for an anesthetic malignant hyperthermia crisis, with mortality rate of 25%. The most common signs of a malignant hyperthermia crisis were hyperthermia, tachycardia, and muscle stiffness. Susceptibility to malignant hyperthermia was confirmed in 79.4% of the 92 relatives investigated with the in vitro muscle contracture test. Conclusion: The crises of malignant hyperthermia resembled those described in other countries, but with frequency lower than that estimated in the country.